Varieties of Fortune of the Ortodox Church in Lithuania in 1918-1940 About a Defence of Andrius Marcinkevičius Doctoral Thesis "The Ortodox Church in Lithuania in 1918-1940") - Gaidis, Ryšard (Lietuvos istorijos studijos, 2006)
-